The impact of radiological assessment schedules on progression-free survival in metastatic breast cancer: A systemic review and meta-analysis. (November 2021) - Dabush, Dor Reuven; Shepshelovich, Daniel; Shochat, Tzippy; Tibau, Ariadna; Amir, Eitan; Goldvaser, Hadar
Highlights: The impact of interval of restaging in metastatic breast cancer on PFS is unclear. Shorter restaging interval was associated with better PFS in pre-specified subgroups. No difference in overall survival was observed. Shorter restaging intervals may lead to over-estimated PFS benefit. Standardization of PFS measurement in clinical trials for breast cancer is desired. Abstract: Background: The impact of interval of restaging on the observed magnitude of benefit of progression-free survival (PFS) is undefined. Materials and Methods: Phase 3 randomized controlled trials (RCTs) investigating anti-neoplastic drugs for metastatic breast cancer which reported the restaging interval and hazard ratio (HR) for PFS were included. Data on study design and study population were collected. HRs and 95% confidence intervals for PFS and OS (overall survival) were pooled in a meta -analysis. Studies were categorized according to short (<9 weeks) or long (≥9 weeks) restaging interval. The differences in PFS and OS effect between trials employing short and long restaging intervals were assessed as subgroup analyses. Analyses were repeated for pre-specified subgroups. Results: Eighty-nine studies comprising 95 comparisons and 44, 901 patients were included. The magnitude of PFS benefit was larger in trials which employed short compared to long restaging intervals, but this difference did not reach the pre-defined threshold for statistical significance (HR = 0.79 vs. 0.86, P =  0.15). Short restaging interval was associated with significantly higher magnitude of effect on PFS in pre-specified subgroups including non-first line trials (HR = 0.78 vs. 0.92, P =  0.04), trials with drugs replacing standard treatment (HR = 0.86 vs. 1.04, P =  0.02) and studies performed in exclusively human epidermal growth factor receptor 2 (HER2) positive disease (HR = 0.72 vs. 0.90, P =  0.02). The magnitude of OS benefit was similar with short and long restaging intervals. Conclusions: Shorter restaging intervals are associated with a higher magnitude of effect on PFS, but not OS. Awareness of the impact of the restaging interval on quantification of PFS is important for the design and interpretation of RCTs.